Inter-relation between Altered Nutritional Status and Clinical Outcomes in Patients with Acute Myocardial Infarction Admitted in a Tertiary Intensive Cardiac Care Unit - Rus, Victoria; Opincariu, Diana; Hodas, Roxana; Nyulas, Tiberiu; Hintea, Marian; Benedek, Theodora (Journal Of Cardiovascular Emergencies, 2018)
The impact of nutritional status on the early outcome of subjects with acute myocardial infarction (AMI) is still not completely elucidated. This study aimed to assess the correlation between nutritional status, as expressed by the CONUT and PIN scores, and (1) clinical and laboratory characteristics, (2) complication rates, and (3) length of hospitalization, in patients with AMI. We included 56 consecutive patients with AMI who underwent primary percutaneous intervention and stenting. Evaluation of the nutritional status was comprised in the calculation of the CONUT and PNI scores. The study population was divided into 2 groups according to the calculated CONUT score, as follows: group 1 – CONUT score <3 points (normal to mildly impaired nutritional status) and group 2 – CONUT score ≥3 points (moderate to severe malnutrition). The primary end-point of the study was the rate of in-hospital complications (left ventricular free wall rupture, hemodynamic instability requiring inotropic medication, high-degree atrioventricular block, the need for temporary cardiostimulation, supraventricular and ventricular arrhythmias and in-hospital cardiac arrest). The secondary end-points included the duration of hospitalization and the length of stay in the intensive cardiac care unit. In total, 56 patients (44.64% with STEMI, 55.35% with NSTEMI) with a mean age of 61.96 ± 13.42 years, 58.92% males were included in the study. Group distribution was: group 1 – 76.78% (n = 43), group 2 – 23.21% (n = 23). There were no differences between the two groups regarding age, gender, cardiovascular risk factors, or comorbidities. PNI index in group 1 was 54.4 ± 10.4 and in group 2 41.1 ± 2.8, p <0.0001. Serum albumin was significantly lower in group 1 – 4.1 ± 0.3 vs. group 2 – 3.6 ± 0.3 (p <0.0001), similarly to total cholesterol levels (group 1 – 194.9 ± 41.5 vs. group 2 – 161.2 ± 58.2, p = 0.02). The complete blood cell count showed that group 2 presented lower levels of hematocrit (p = 0.003), hemoglobin (p = 0.002), and lymphocytes (p <0.0001) compared to group 1, but a significantly higher platelet count (p = 0.001), mean platelet volume (p = 0.03), neutrophil/lymphocyte (p <0.0001) and platelet/lymphocyte (p <0.0001) ratios, indicating enhanced blood thrombogenicity and inflammation. Regarding in-hospital complications, group 2 presented a higher rate of hemodynamic instability (group 1 – 11.6% vs. group 2 – 38.4%, p = 0.02). The overall hospitalization period was 7.7 ± 1.4 days in group 1 vs. 10.2 ± 4.8 days in group 2, p = 0.06; while the duration of stay in the intensive cardiac care unit was 2.6 ± 0.5 days in group 1 vs. 4.0 ± 2.5 days in group 2, p = 0.02. This study proved that nutritional deficit in acute myocardial patients who undergo revascularization is associated with an increased rate of in-hospital complications and with a longer observation time in a tertiary intensive cardiac care unit.